Analysis of the effective use of attracted investments in the innovative development of regions - Khatamova Manzura Ochildievna; Normurodov Asliddin Alijon oglu (THE INNOVATION ECONOMY, 2026)
The article analyzes the investments made to the economy by districts (cities) of Surkhandarya region using descriptive statistics. The analysis using this method determined the positions of each district (city) of the region in groups according to statistical indicators. This, in turn, helps to draw up investment programs for this district (city).